An Effect of Job Characteristics and Interpersonal Relations Organizational Commitments in PT. AEP (Anglo Eastern Plantation) Ukindo Blankahan Estate - Muhammad Nazril Ilham; Muhammad Isa Indrawan; Husni Muharram Ritonga (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Organizational commitment refers to the thinking of individuals in the organization and working effectively and positively for the organization. Employee organizational commitment is a key factor that contributes to the achievement of organizational goals. The final performance of an organization depends on the level of commitment of its employees. This study is focused on knowing the characteristics of work and interpersonal relationships affect the organizational commitment of employees in plantation sector organizations in Indonesia, especially at PT. AEP (Anglo Eastern Plantation) Ukindo Blankahan Estate North Sumatra, Indonesia. Characteristics of work consisting of skill variety, task identity, task significance, autonomy, feedback and interpersonal relationships are the 6 main independent variables in this study. Affective commitment and normative commitment are the two main dependent variables for this study. A structured questionnaire survey was conducted to collect primary data from 100 randomly selected employees covering the plantation sector in Indonesia, especially at PT. AEP (Anglo Eastern Palntation) Ukindo Blankahan Estate North Sumatra, Indonesia. Data were analyzed using Confirmatory Factor Analysis (CFA). The findings reveal that skill variation (NOW), interpersonal relations (IRP) and autonomy (WOE) are significant and positive factors that can increase the affective commitment of employees in plantation sector organizations. Skill variation (NOW), task identity (PAA), autonomy (WOE) and feedback (RME) were significant and positive factors that increased normative commitment.